Gambaran Asupan Makanan dan Status Gizi pada Ibu Hamil di Huntara Kelurahan Petobo Kota Palu: Overview of Food Intake and Nutritional Status of Pregnant in the Temporary Shelter, Petobo Village, Palu City - Dwi Erma Kusumawati; Nurwidianti Nurwidianti; Fahmi Hafid (Poltekkes Kemenkes Palu, 2022)
Introduction: Sufficient nutrient intake is vital for fetal growth and development during pregnancy. Stable food security supports adequate food consumption. Natural disaster that struck Palu City in 2018 had a negative influence on food security. Food intake and nutritional status among pregnant women in temporary housing in Petobo sub-district, South Palu sub-district are described in this study. Methods: The research method used in this study is descriptive. All pregnant women in temporary shelters were included in the population and samples, which totally 30 pregnant women. Data collected including MUAC and Food Recall for 24 hours over two non-consecutive days. The study results showed that the average intake was 1,370 kcal of energy, 232.7 grams of carbohydrates, 38.6 grams of protein, and 28.4 grams of fat. The majority for energy and macronutrient consumption are below 80% of the Indonesian RDA 2019. The average of Vitamin A 575.6 mcg, vitamin C 33.3 mg, vitamin B6 0.9 mg, calcium 679.5 mg, and zinc 4.2 mg are below 80% of the Indonesian RDA 2019. Only intake of Vitamin B9 and Iron is sufficient with an average intake of 511.3 mcg and 42.3 mg. The nutritional status of all pregnant women are not at risk of CED. In conclusion, intake of calories, macronutrient, and micronutrient are classified as inadequate except for vitamin B9 and Iron, and all pregnant women is not at risk of CED. It is suggested the diversify of diet by eating more locally grown foods and doing enough exercise. ABSTRAK Pendahuluan: Asupan zat gizi pada saat ibu hamil di perlukan untuk pertumbuhan dan perkembangan janin. Asupan makanan yang cukup di dukung adanya kestabilan ketahanan pangan. Bencana alam yang terjadi di kota palu pada tahun 2018 berdampak pada ketidakstabilan ketahanan pangan. penelitian ini menggambarkan asupan makanan dan status gizi pada ibu hamil di hunian sementara kelurahan Petobo kecamatan Palu Selatan. Metode: Penelitian ini menggunakan jenis penelitian deskriptif. Populasi dan sampel adalah semua ibu hamil yang berada di hunian sementara berjumlah 30 ibu hamil. Pengumpulan data berupa LILA dan Recal 24 jam selama 2 hari tidak berurutan. Hasil penelitian menunjukkan rata-rata asupan energi 1.370 kkal, karbohidrat 232,7 gr, protein 38,6 gr dan lemak 28,4 gr. sebagian besar asupan energi dan zat gizi makro masih <80% dari AKG. Asupan vitamin A 575,6 mcg, vitamin C 33,3 mg, vitamin B6 0,9 mg, kalsium 679,5 mg dan zink 4,2 mg masih < 80% dari AKG. Hanya asupan Vitamin B9 dan fe cukup dengan rerata asupan 511,3 mcg dan 42,3 mg serta Status gizi semua ibu hamil tidak berisiko KEK. Kesimpulan bahwa semua asupan energi, zat gizi makro dan sebagian besar dari zat gizi mikro berkategori kurang. Asupan vitamin B9 dan Fe ibu hamil cukup dengan status gizi semua ibu hamil tidak berisiko KEK. Disarankan untuk tingkatkan keanekaragaman makanan dari pangan lokal dan lakukan aktivitas fisik yang cukup.